Differences in the Management of Perforated Appendicitis in Children by Race and Insurance Status. Issue 9 (September 2017) - Lassiter, Randi L.; Hatley, Robyn M.
This study was conducted to assess whether race and socioeconomic status influence the management method used to treat pediatric perforated appendicitis. Nonelective pediatric admissions with a primary diagnosis of appendicitis were analyzed using data from the 2001–2010 Nationwide Inpatient Sample. Bivariate and multivariate analyses were used to determine the association between race, insurance status, median household income, rural/metropolitan location, and the risk adjusted odds of undergoing surgery, laparoscopic appendectomy, percutaneous drainage, or neither surgery nor percutaneous drainage. A total of 46, 211 admissions of perforated appendicitis were identified. Surgery was performed in 90.5 per cent of them. Black children were less likely to have surgery [adjusted odds ratio (AOR) = 0.53] and more likely to be managed non-surgically with percutaneous drainage (AOR = 1.79). Self-pay patients were less likely to have laparoscopic surgery (AOR = 0.80). Children from rural counties were more likely to undergo surgery than those from larger metropolitan areas (AOR = 1.30). Higher estimated household income did not predict the method of treatment. Although previous studies have attributed racial disparities in outcomes for appendicitis to different rates of perforation and access to care, these findings demonstrate significantly dissimilar management strategies for patients presenting with a similar disease process.